2007
DOI: 10.1002/bem.20287
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed and continuous wave mobile phone exposure over left versus right hemisphere: Effects on human cognitive function

Abstract: The possible effects of continuous wave (CW) and pulse modulated (PM) electromagnetic field (EMF) on human cognition was studied in 36 healthy male subjects. They performed cognitive tasks while exposed to CW, PM, and sham EMF. The subjects performed the same tasks twice during each session; once with left-sided and once with right-sided exposure. The EMF conditions were spread across three testing sessions, each session separated by 1 week. The exposed hemisphere, EMF condition, and test order were counterbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 19 publications
4
58
1
3
Order By: Relevance
“…While the present study's findings are consistent with early reports that exposure to PM RF affects working memory performance (Koivisto et al, 2000, Regel et al, 2007a, Regel et al, 2007b, the majority of the literature has not found such an influence (Haarala et al, 2003, Haarala et al, 2004, Haarala et al, 2007, Krause et al, 2007, Leung et al, 2011). Although we cannot be conclusive, a number of reasons related to the methodological improvements employed by this study may explain the results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While the present study's findings are consistent with early reports that exposure to PM RF affects working memory performance (Koivisto et al, 2000, Regel et al, 2007a, Regel et al, 2007b, the majority of the literature has not found such an influence (Haarala et al, 2003, Haarala et al, 2004, Haarala et al, 2007, Krause et al, 2007, Leung et al, 2011). Although we cannot be conclusive, a number of reasons related to the methodological improvements employed by this study may explain the results.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of studies using this task, however, have not found any effects of PM RF exposure on performance (Haarala et al, 2003, Haarala et al, 2004, Haarala et al, 2007, Krause et al, 2007, Leung et al, 2011.…”
Section: Introductionmentioning
confidence: 94%
“…However, the majority of MP studies did not report any effects on N-back performance (e.g. Krause et al, 2000aKrause et al, , 2007Haarala et al, 2003Haarala et al, , 2004Haarala et al, , 2007. To date, only one group has used EEG measures to test whether there are MP-effects on neural processes relating to subtle cognitive processing during N-back tasks, with no consistency of results.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these studies examined the effects of Global System for Mobile Communications (GSM)-like signals [Hamblin et al, 2006;Wilen et al, 2006;Fritzer et al, 2007;Haarala et al, 2007;Irlenbusch et al, 2007;Krause et al, 2007;Regel et al, 2007a,b;Barth et al, 2008;Cinel et al, 2008;Curcio et al, 2008;Kleinlogel et al, 2008;Luria et al, 2009;Wiholm et al, 2009], whereas only a few analysed the impact of Wideband Code-Division Multiple Access/3rd Generation Universal Mobile Telecommunications System (WCDMA/3G UMTS) handset signals on cognitive function [Schmid et al, 2005;Kleinlogel et al, 2008;Unterlechner et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the possible effects of RF-EMF of GSM mobile phones on cognition did not find any difference in performance measures between real and sham exposure [Hladky et al, 1999;Croft et al, 2002;Haarala et al, 2003Haarala et al, , 2004Haarala et al, , 2007Hinrichs and Heinze, 2004;Besset et al, 2005;Russo et al, 2006;Cinel et al, 2007Cinel et al, , 2008Fritzer et al, 2007;Irlenbusch et al, 2007;Curcio et al, 2008;Kleinlogel et al, 2008]. On the other hand, there are an almost equal number of studies reporting effects on cognitive functions, however, the effects are not consistent.…”
Section: Introductionmentioning
confidence: 99%